Disease Trends in Children and Adolescents in Japan: A Retrospective Observational Study Using the Nationwide Claims Data for 2012-2016 - Maiko Suto; Kenji Takehara; Naho Morisaki; Akinori Moriichi; Ruoyan Gai; Rintaro Mori (MDPI AG, 2024)
This study aimed to clarify diseases that occur more frequently by age and identify the peaks and trends of each disease from infancy to adolescence for early detection and treatment. This retrospective observational study was conducted using Japan's National Database of Health Insurance Claims Specific Health Checkups from January 2012 to December 2016. Using peak ages and trends in the number of patients, we grouped diseases by the International Classification of Diseases chapters. Although diseases that peaked during infancy were the most common (10 disease chapters), other diseases peaked at school-going age and adolescence. Diseases in four chapters peaked during adolescence and continued to increase toward the age of 18. These four chapters included mental, behavioral, and neurodevelopmental disorders; diseases of the nervous system; the genitourinary system; and pregnancy, childbirth, and the puerperium. Childhood-onset diseases can affect long-term health and healthcare needs, and timely screening and guidance based on disease trends can provide an effective intervention. To establish a child healthcare system that provides preventive support for children and adolescents' physical, psychological, and social health, further research is needed to comprehensively understand the issues per age and developmental stage.